2017
DOI: 10.1002/ijc.30775
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus for the treatment of progressive kaposiform hemangioendothelioma: A multicenter retrospective study

Abstract: Kaposiform hemangioendothelioma (KHE) is an aggressive disease with high morbidity and mortality. The aim of this study was to retrospectively evaluate the efficacy and safety of sirolimus for the treatment of progressive KHE. A multicenter, retrospective cohort study was conducted in patients with progressive KHE treated with sirolimus. A total of 52 patients were analyzed. Thirty-seven (71%) patients exhibited Kasabach-Merritt phenomenon (KMP) and were significantly younger than the patients without KMP [95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
126
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(132 citation statements)
references
References 45 publications
6
126
0
Order By: Relevance
“…This is consistent with other literature that has shown effectiveness of mTOR inhibition in patients with KHE refractory to standard or alternative treatment modalities . In a multicenter retrospective analysis, patients who received sirolimus as part of treatment tended to have improvement in clinical symptoms and tumor size, suggesting that sirolimus therapy should be considered …”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with other literature that has shown effectiveness of mTOR inhibition in patients with KHE refractory to standard or alternative treatment modalities . In a multicenter retrospective analysis, patients who received sirolimus as part of treatment tended to have improvement in clinical symptoms and tumor size, suggesting that sirolimus therapy should be considered …”
Section: Discussionsupporting
confidence: 90%
“…Evidence for the efficacy of sirolimus in treatment of KHE is plentiful, albeit no controlled studies exist . However, it is noteworthy that patients should not receive a live vaccine while being treated with sirolimus.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that Sirolimus is a well-tolerated. The common grade three side effects bone marrow toxicity in 27%, gastrointestinal toxicity in 3% and metabolic toxicity in 3% [74,75].…”
Section: Role Of Mtor Inhibitorsmentioning
confidence: 99%